Design of a Low Loss RF Mixer in Ku-Band (12 - 18 GHz) - Shah, Sanjeev K.; Chauhan, Rudra P.; Singh, Sanjay; Pandey, Lalit; Singh, Sandeep (Scientific Research Publishing, 2012)
The goal of this paper is to design and develop low conversion loss mixers at Ku Band (12 - 18 GHz) in microstrip line configuration. The Ku-band (Kurtz-under band) is primarily used for satellite Communications, particularly for editing and broadcasting satellite television. CAD tools (Agilent’s Advance Design System software) have been used for simulation and optimization of the circuits. 180 degree balanced mixer configuration has been adopted due to better RF to LO isolation requirement. The circuit is designed on microstrip line using RT Duroid (Dielectric Constant = 2.22). Initially a rat race coupler (180 degree hybrid) was designed and simulated and optimized for required performance successfully.
Keywords: Single Balanced Mixer; Double Balanced Mixer